Perlindungan Hukum terhadap Hak Pekerja Perempuan Di Masa Pandemi Covid-19 - Conie Pania Putri (Universitas Batanghari Jambi, 2020)
The world is currently being faced by a global covid-19 pandemic, including in Indonesia this pandemic is very disturbing to the public. Manpower development must be regulated in such a way that basic rights and protections for workers are fulfilled, especially for women workers so as to create conducive conditions. The purpose of this paper is to find out the policies issued by companies for workers, especially women workers during the Covid-19 pandemic. This writing method is library research, which is a series of research related to library data collection methods, or research where the object of research is excavated through a variety of library information. The results obtained in this paper are that the company policies that terminate employment of women during the Covid-19 pandemic are protected by Law Number 13 of 2003 concerning Manpower, the losses caused by the company have not reached 2 years, the company cannot simply terminate the work relationship, Then there needs to be other efforts provided by companies or the government in overcoming the impact of Covid-19 on laid-off workers so that they can limit working time / overtime and workers can be sent home without breaking the work relationship The suggestion is expected that the government should supervise and act decisively against companies that employ female workers.